RANCANGAN PENGEMBANGAN LAYANAN PADA APLIKASI SIMENDAH - Hasibuan, Rifky Rhomadoni; Marthiawati. H, Noneng; Gustinar, Gustinar (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2023)
The accumulation of waste is one of the problems in Mendalo Indah Village due to the unstructured pattern of waste disposal. To overcome this, the author made a research that would later give birth to an innovative garbage ojek service, become one way to reduce piles of garbage, and keep the environment cleaner and healthier. When conducting research, the author uses a qualitative method that collects data through interviews, research, and observation based on field events. The analysis method in this research uses the Unified Modeling Language (UML) method which consists of Use Case Diagram, Activity Diagram and Class Diagram. The design design is only limited to prototypes. The results of this study produced a garbage ojek service feature in the SiMendah application. With this garbage ojek service feature, it will make it easier for people to dispose of garbage by simply ordering a garbage ojek through the SiMendah application, the ojek driver will pick up and dispose of the garbage where it should be. When this service is run, it is expected to help overcome the pile of garbage